(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The application of ecological concepts to the examination of animal species and their surroundings is the scientific discipline of wildlife ecology. A frequent goal of research is to create practical techniques for managing natural systems in order to achieve and maintain balance among wildlife, ecosystems, as well as humans, and this often results in baseline data that may be used to guide wildlife management strategies. The term "wildlife" isn’t precisely defined, and it’s been applied to anything from vertebrates to all wild creatures and plants over time. Wildlife management has generally centered on game species, particularly traditionally targeted mammals and birds, with both the goal of increasing their populations to promote sport as well as subsistence hunting opportunities. In the 1960s, wildlife conservation as well as research shifted to nongame animals and other taxa, such as reptiles, amphibians, or even invertebrates. Critically endangered species are a key problem in today’s wildlife conservation, and they are usually given priority over gaming species in management plans. Many new quantitative techniques have been developed in the last decade, and they are becoming more important in wildlife management, conservation, and research. The fundamental ideas and concepts, as well as applications and contemporary trends in animal ecology research, will be covered in this article.